Reduced aggregation of the leghorn male hepatoma cell line in suspension by supplementing dextran sulfate in the media - Jung Soo Lim; Ji Soo Kim; Yugyeong Cheon; Tae Sub Park; Jong Kwang Hong (Animal Bioscience)
Objective The study aimed to improve the efficiency of leghorn male hepatoma (LMH) cells for animal virus vaccine production by transitioning from adherent to suspension culture and evaluating the effects of dextran sulfate (DS) on preventing cell aggregation. The goal was to enhance cell growth, viability, and glucose metabolism and to develop efficient suspension-adapted LMH cells for large-scale vaccine production. Methods LMH cells previously cultured in an adherent state were transferred to 125 mL Erlenmeyer flasks to conduct suspension culture. Cell culture performance, including cell density, viability, and glucose metabolism, during the cultures was measured, along with an assessment of cell aggregation. Additionally, mRNA expression levels of genes associated with cell adhesion and apoptosis were monitored. Results DS supplementation in suspension culture enhanced cell viability and growth, with higher cell densities and viabilities compared to control media. Additionally, DS supplementation reduced glucose consumption and waste production, indicating improved metabolic efficiency. DS also delayed cell aggregation, possibly by downregulating integrin expression and promoting anti-apoptotic gene expression. However, even after 2 months, cell aggregation persisted in both control and DS-supplemented cultures, suggesting further optimization is needed for LMH cell adaptation to suspension culture. Conclusion DS supplementation in LMH cell suspension cultures led to notable improvements in cell growth, viability, and glucose metabolism, while also decreasing the cell aggregation.